Characteristics of slag produced from incinerated hospital waste - Idris, Azni; Saed, Katayon (Elsevier Science B.V., 2002)
Ash produced from a hospital waste incinerator was treated using a high temperature melting process at 1200°C. The quality of the produced slag was characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), leaching tests and sequential chemical extraction of metals. The slag contained large amounts of SiO2, CaO, Al2O3, Sn, Ni, Cu, Ba and B. XRD analysis revealed a moderate crystal structure for the melted slag and identified the main crystals as quartz (SiO2), kaolinite (Al2Si2O5(OH)4), albite (NaAlSi3O8) and gibbsite (Al(OH)3). The observed crystal structure assists in preventing the leaching of heavy metals from the slag. Furthermore, the leaching results found the produced slag to comply with disposal limits set by the US EPA. Results from sequential chemical extraction analysis showed that metals in the slag exhibited the strongest preference to be bound to the residual fraction (stable fraction), which is known to have very low leaching characteristics. Melting was found to stabilize heavy metals in hospital waste successfully and therefore it can be an acceptable method for disposal.